M-Learning in Africa: Doing the Unthinkable and Reaching the Unreachable - Brown, Tom H. (International Handbook of Information Technology in Primary and Secondary Education, 2008)
Mobile learning (m-learning) has started to play a vital role in Africa. It should be noted that m-learning has brought e-learning to the rural communities of Africa – to learners who we never imagined as e-learning learners only a few years ago. M-learning is the gateway to e-learning for most learners in Africa as the rapidly growing wireless infrastructure increasingly fulfils their access needs. Africa is actually leap-frogging from an unwired, nonexistent e-learning infrastructure to a wireless e-learning infrastructure. The statistics in this regard are already significant proof of this process. This chapter provides examples of m-learning projects in rural Africa and the successful use of basic technologies (basic and cheap mobile phones that can only do SMS and voice communication) to enhance learning and learning support.
Keywords: TICE; numérique